Travel Intention in Following of New Normal Era: The Role of Perceived Risk, Travel Motivation and Travel Constraints - Puji Ratna Sari; Arief Helmi; Rita Komaladewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
There are behavioral changes in tourism in the new normal era, so questions arise related to tourist behavior. The purpose of this study is to examine risk perception in influencing tourist intention to visit, what motivates tourists to have the intention to visit and whether travel constraints become obstacles in influencing tourist intention to visit. The gap in previous research and the lack of research on how the relationship between variables in the new normal era. This research is a quantitative research method. descriptive and verification on 235 respondents on Bali tourism in the new normal era using structural equation model analysis or SEM (Structural Equation Modeling) processed using smartPLS. The results showed that (1) perceived risk has a negative effect on travel intention (2) travel motivation push factors have a positive effect on travel intention (3) travel motivation pull factors have a positive effect on travel intention (4) travel constraints have a positive effect on travel intention. Perceived risk tends to be low, travel constraints are quite high, so travel motivation, especially pull factors, is very influential in increasing tourist travel intention.